Correlation between maternal and neonatal blood vitamin D levels and its effect on the newborn anthropometry - Sathish, Paulraj; Raveendran, Sajeethakumari; Padma, Ramasamy; Balakrishnan, Doraisami; Muthusami, Muthulakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Vitamin D deficiency during pregnancy has important implications for the new born and infant. In India, there were few data about the prevalence of hypovitaminosis D in pregnancy and in new-born and its correlation. Hence, this study aim was to determine vitamin D deficiency in pregnant women and their new-borns and to assess the correlation between maternal and new born serum levels of the vitamin D3 and also to study its effect on the newborn anthropometry. Methods: This cross-sectional, hospital based study was conducted with 54 consecutive women in labour presenting with a singleton term pregnancy at a large tertiary centre in Tamilnadu, India. Data were recorded on a special form and 25-hydroxy vitamin D3 was assessed before delivery in mothers and after delivery in their infant’s umbilical cord blood. Results: The mean vitamin D levels were 20.21 ng/mL for the participants and 20.07 ng/mL for the newborns. Vitamin D severe deficiency was noted in 3 (6%), deficiency 31 (57%), insufficiency 12 (22%) and sufficiency in 8 (15%) of 54 participants whereas severe deficiency, insufficiency and sufficiency respectively, were noted in 4 (7%), 30 (56%), 11 (20%) and 9 (17%) of the newborns. Maternal vitamin D level significantly associated with socioeconomic status, term of delivery and type of delivery respectively were p=0.000, p=0.000 and p=0.038 whereas age (p=0.081), BMI (p=0.085) and parity (p=0.038) was not significant at p <0.05 level by chi-square analysis. Similarly, the new born characteristics of birth weight (p=0.000), birth length (p=0.016), head and chest circumference (p=0.001, p=0.000) exists significant association at p<0.05 level by analysis of variance (ANOVA) method and also there was a strong positive correlation between the vitamin D levels in maternal and cord blood (r=0.898; P <0.05). Conclusions: There was a high prevalence of vitamin D deficiency in the south Indian pregnant women and their newborns. Vitamin D deficiency increased the risk of low birth weight neonate and it also had an effect on the length of the baby, head circumference and chest circumference. This public health problem needs urgent attention.